Effects of vinasse upon the decomposition rate of Ocotea pulchella leaves in cerrado soil - Schoenlein-Crusius, I. H.; Tauk, S. M. (My University, 1991)
Ocotea pulchella leaves placed on soil treated with vinasse lost 64.48% of their organic matter, whereas the leaves sampled in the control parcels lost 70.68%, after one year. -from Authors
Keywords: cerrado; decomposition; vinasse; Ocotea pulchella